Intersection control with connected and automated vehicles: a review - Wu, Jiaming; Qu, Xiaobo (Journal of Intelligent and Connected Vehicles, 2022)
Purpose This paper aims to review the studies on intersection control with connected and automated vehicles (CAVs). Design/methodology/approach The most seminal and recent research in this area is reviewed. This study specifically focuses on two categories: CAV trajectory planning and joint intersection and CAV control. Findings It is found that there is a lack of widely recognized benchmarks in this area, which hinders the validation and demonstration of new studies. Originality/value In this review, the authors focus on the methodological approaches taken to empower intersection control with CAVs. The authors hope the present review could shed light on the state-of-the-art methods, research gaps and future research directions.